Reading Attitudes, Habits and Classroom Practices among Ecuadorian Master’s Students - Romero-Castro, Walter Roberto; Argudo-Serrano, Juanita Catalina (Revista Arbitrada Interdisciplinaria Koinonía, 2022)
The purpose of this study is to determine how master's students' personal reading attitudes and habits impact their classroom instructional practices. An online questionnaire was used to collect data on participants' habits and attitudes toward reading in English. Only 24% read between 30 minutes and more than an hour, a small number of teachers (8) consider themselves to be "devoted" readers, teachers who value reading more are more likely to use best practice strategies. However, teachers who value reading less tend to share their own perceptions related to reading and also recommend reading material to students, and teachers who read for pleasure more than 30 minutes a day use a greater number of instructional practices considered to be among the best.